Can Romania offer a sustainable environment for the FDI inflows? - DIACONU (MAXIM), Laura (European Journal of Sustainable Development, 2016)
It is well known that the foreign direct investments (FDI) represent a key factor for the economic growth of the developing states. Despite Romania’s efforts of creating a favourable environment for the foreign investors, the global economic and financial crisis has considerably diminished its attractiveness for the multinational companies. Considering these aspects, the purposes of the present paper are to identify the factors that currently attract the foreign investors in Romania and to analyse if they can be valued on long term. In order to reach these goals, several research methods were used. First of all, after analysing the specialised literature, we have conducted in-depth interviews on managers and experts from 14 multinational companies that are present in Romania, in order to identify the determinants of the FDI. Secondly, to see if these factors might represent long term advantages, we have we analysed the secondary data offered by various statistical yearbooks, reports and by different empirical investigations. The relevance of this study results from the fact that the conclusions may offer valuable information for the Romanian policy makers to create a favourable environment for the FDI inflows, on long term. Keywords: FDI determinants, Romania, human capital, low production costs, long term favourable environment